Determinants of Dysmenorrhea Pain Levels of in Adolescents - Dwi Wahyu Wulan Sulistyowati; Ani Media Harumi (Aloha International Journal of Health Advancement (AIJHA), 2020)
Menstrual pain sometimes makes women unable to move normally so that quality deteriorates in their daily lives. Complaints that appear vary in intensity and are different for each person. Some women only feel mild pain, but others feel very severe pain, stomach like squeezing, vomiting, discomfort in the stomach, pain in the breast, even fever and headaches. The design of this study was cross-sectional. The population used in this study were all middle school and vocational high school students who experienced dysmenorrhea every time menstruation in the last 2 months period as many as 190 students and a sample of 130 female students. Sampling used was a simple random technique, namely the determination of samples taken randomly. The dependent variable was dysmenorrhea pain levels, while the independent variable were anxiety, activity, age, and nutritional status. The instrument used was a questionnaire and checklist. The analysis technique used was the multiple linear regression test. From the results of the study, there was a strong influence of anxiety, age, and nutritional status on the dysmenorrhea pain levels. Whereas there was no influence of activity on dysmenorrhea pain levels. Keywords: dysmenorrhea; pain; anxiety; nutrtional; activity; age